RACES OF PHYTOPHTHORA INFESTANS IN INDIA – PRESENT SCENARIO - Singh, P H; Singh, B P (Potato Journal, 2013)
In India, in 1958, Phytophthora infestans races ‘0’ and ‘1’ were present in North-western hills while race ‘0’ was present in North-eastern hills. The racial pattern was simple until 1966. Complex races were recorded from all pockets of the country during seventies. In 2005-06, a total of 29 races possessing 7 to 11 genes were recorded from various parts of the country. Frequency of 11 gene complex race 1. 2. 3. 4. 5. 6. 7. 8. 9. 10. 11 was the highest.